Coherent regime and far-to-near-field transition for radiative heat transfer. (January 2017) - Tsurimaki, Yoichiro; Chapuis, Pierre-Olivier; Okajima, Junnosuke; Komiya, Atsuki; Maruyama, Shigenao; Vaillon, Rodolphe
Abstract: Radiative heat transfer between two semi-infinite parallel media is analyzed in the transition zone between the near-field and the classical macroscopic, i.e. incoherent far-field, regimes of thermal radiation, first for model gray materials and then for real metallic (Al) and dielectric (SiC) materials. The presence of a minimum in the flux-distance curve is observed for the propagative component of the radiative heat transfer coefficient, and in some cases for the total coefficient, i.e. the sum of the propagative and evanescent components. At best this reduction can reach 15% below the far-field limit in the case of aluminum. The far-to-near-field regime taking place for the distance range between the near-field and the classical macroscopic regime involves a coherent far-field regime. One of its limits can be practically defined by the distance at which the incoherent far-field regime breaks down. This separation distance below which the standard theory of incoherent thermal radiation cannot be applied anymore is found to be larger than the usual estimate based on Wien׳s law and varies as a function of temperature. The aforementioned effects are due to coherence, which is present despite the broadband spectral nature of thermal radiation, and has a stronger impact for reflective materials. Highlights: The coherent regime of thermal radiation between two surfaces is analyzed in detail. Gray materials and then typical metallic and dielectric materials are considered. A minimum observed on the flux-distance curve is due to propagative waves. Distances characterizing the far-to-near-field transition are provided. The incoherent regime can break down at distances larger than Wien's law estimates.